SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN BERPRESTASI DENGAN METODE PROFILE MATCHING PADA PT. SARANA INTI PERSADA (SIP) - Handayani, Rani Irma (LPPM Universitas Nusa Mandiri, 2017)
Having a Human Resources (HR) quality is required by the company to improve the productivity performance of a company. PT. Sarana Inti Persada (SIP) is a company engaged in telecommunications. In the employee performance evaluation is still subjective, because the limited time and the limited ability to accurately view all aspects often led to errors in decision making. Therefore, in assessing the performance of employees needed some aspects in order to obtain accurate results. Necessary Decision Support System (DSS) for the selection of the performance appraisal performing employees. In a profile matching, identification of the employee groups for better or worse. The employees in the group are measured using several assessment criteria. If pelakasana good obtaining different scores from implementing bad or a characteristic, then the variable is beneficial to choose a good executor.